1970
DOI: 10.3126/jnps.v30i3.3916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Birth Asphyxia in Dhulikhel Hospital: A Retrospective Study

Abstract: Introduction: Birth asphyxia is defined by the World Health Organization "the failure to initiate and sustain breathing at birth." The WHO has estimated that 4 million babies die during the neonatal period every year and 99% of these deaths occur in low-income and middle income countries. Three major causes account for over three quarters of these deaths, serious infection (28%) complication of preterm birth (26%) and birth asphyxia (23%). This estimation implies that birth asphyxia is the cause of around one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
27
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 7 publications
11
27
5
Order By: Relevance
“…This is consistent with studies done by S. Dongal, et al from Nepal and Nilufar, Shireen, et al from Bangladesh [10,11] . Meconium staining of amniotic fluid was present in 68(10.8%) deliveries out of which28( 41.1%) were non vigorous babies, which correlates with study done by Vineet Gupta, et al at institute of medical sciences, Banaras Hindu university, Varanasi [12] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with studies done by S. Dongal, et al from Nepal and Nilufar, Shireen, et al from Bangladesh [10,11] . Meconium staining of amniotic fluid was present in 68(10.8%) deliveries out of which28( 41.1%) were non vigorous babies, which correlates with study done by Vineet Gupta, et al at institute of medical sciences, Banaras Hindu university, Varanasi [12] .…”
Section: Discussionsupporting
confidence: 93%
“…Though it is higher when compared to other studies where they reported the prevalence of birth asphyxia as 26.9/1000 live births. The higher incidence in our study could be explained by large number of deliveries conducted and referral of large number of complicated pregnancies to this center unlike other hospitals from where previous studies were published [10] .Comparison of basic demographic profile, antenatal risk factors and foetal risk factors between study group and control group showed that they are comparable except multiple births. But none of the twin babies suffered birth asphyxia in this study.…”
Section: Discussioncontrasting
confidence: 48%
“…This figure is very high when compared with prevalence of 0.24% in Canada, 0.85% in the Netherlands, 2.5% observed in Dire Dawa, Ethiopia, and 2.69 in Nepal but lower than the study in Nigeria which was 29.4% [10, 13–16]. In addition, male to female ratio was found to be 1.07:1 which is similar to study in India [17].…”
Section: Discussionsupporting
confidence: 60%
“…Of those, 82 cases (19.25%) were of perinatal asphyxia, which is similar to the study carried at Dhulikhel hospital in which total asphyxiated babies were 14% of the total NICU admission. 10 The rate of birth asphyxia in the present study was low in comparison to the study conducted by Daga AS et al (27%) and Azam in Pakistan (48%).…”
Section: Resultscontrasting
confidence: 52%